APLIKASI EDUKASI MENGENAL MAKANAN KHAS KARAWANG UNTUK RAUDHATUL ATHFAL - Wahyu Arya Pambudi; Didi Juardi; Nono Heryana (Department of Science and Technology Ibrahimy University, 2020)
In the learning process of introducing Karawang special foods, teachers at RA Babussalam Al-Islami use more teacher-centered learning techniques where the teaching methods make children as if they are only listeners in learning, so learning is less attractive and makes children bored. The purpose of this study is to make an educational application that can help children to recognize the special food of Karawang by using the MDLC (Multimedia Development Life Cycle) method which consists of 6 stages of Conceptualization, Design, Material Collection, Assembly, Testing and Distribution. The application is made with an Android-based multimedia format in which presents text, images, audio, and animation that is packaged in the form of an Android-based game so that it can attract children's learning interest in knowing the typical food of Karawang. Testing on this application uses Alpha and Beta testing with the results of all the indicators declared good. The results of the Beta test resulted in scores above 80 on each question, which indicated that the application made was very suitable as a medium for children's learning in recognizing traditional food in Karawang.